Spatial movements and social networks in juvenile male song sparrows - Templeton, Christopher N. (Oxford University Press, 2012)
The time between fledging and breeding is a critical period in songbird ontogeny, but the behavior of young songbirds in the wild is relatively unstudied. The types of social relationships juveniles form with other individuals can provide insight into the process through which they learn complex behaviors crucial for survival, territory establishment, and mate attraction. We used radio telemetry to observe social associations of young male song sparrows (Melospiza melodia) from May to November. Juvenile song sparrows were frequently observed in social flocks and generally associated with more birds in the summer than in the autumn months. Most juvenile subjects formed stable social relationships with other birds and were seen with the same individual on up to 60% of the days observed. The strongest associations occurred with other juvenile males, and these individuals were often seen <1 m from the subject, even when the subject moved large distances between tracking observations. Associations also had long-term behavioral consequences as subjects were more likely to establish territories near their associates and learn shared song types. Our results indicate that male song sparrows spend a large percentage of the juvenile life stage forming social relationships and suggest that these associations may be important for the ecology of young birds and the ontogeny of their behaviors.